A Review of Obstructive Sleep Apnea Treatment: The Role of Surgery in Therapy and Alternative Treatment Modalities - Kacper Zielonka; Joanna Jasińska; Bartosz Dądela; Marcin Markowski; Natalia Śliwa; Emilia Maria Majewska; Eliza Kawalska; Szymon Gnitecki; Szymon Janczura; Maciej Borowski (Quality in Sport)
Obstructive sleep apnea (OSA) is a common sleep disorder involving repeated upper airway obstructions during sleep, leading to hypoxia, fragmented sleep, and excessive daytime sleepiness. It is linked to significant cardiovascular and metabolic risks and affects 17-30% of individuals aged 30-69, with higher rates in the elderly. Diagnosis is typically made using polysomnography, which assesses the frequency and severity of apneic events.